Comparative Analysis between Cone and Sleeve in Managing Severe Bone Defect during Revision Total Knee Arthroplasty: A Systematic Review and Meta-Analysis - Kim, Hyun Jung; Lee, O-Sung; Lee, Seung Hoon; Lee, Yong Seuk (The Journal of Knee Surgery, 2018)
This review aims to compare the outcomes of revision total knee arthroplasty (TKA) performed using a tantalum cone and a titanium sleeve. A rigorous and systematic search was performed. Each of the selected studies was evaluated for methodological quality. Data were extracted according to the following: study design, level of evidence, cases enrolled, age, sex ratio, follow-up, involved part, bone defect, degree of constraint, augments (cone and/or sleeve), pre-clinical score, post-clinical score, radiological results, major complications, and endpoint analysis. Nineteen articles were included in the final analysis. The knee scores of the cone and sleeve groups were increased in all studies with or without statistical significance. For the radiological outcome, radiolucent line was seen in six cases in the cone group and in 15 cases in the sleeve group. Only a few specific augment-related complications were noted. Our results support the use of the newly devised augments in bone defect during revision TKA in terms of clinical and radiological outcome.
Keywords: revision total knee arthroplasty; bone defect; augment; cone; sleeve